Old Radicalsm dan New Radicalsm di Indonesia - Tedy Winanrno (Universitas Islam Malang, 2022)
The arrival of Islam to Indonesia is one of the most successful spreads of religious understanding. This is of course because the preaching that was brought by the Ulama in the early days of Islam entering Indonesia was preaching by prioritizing the values ​​of peace. Respect for native culture is a lure for Indonesian people to fall in love with Islam. After 13 centuries of peaceful development of Islam, intruders came with a mission to change the foundation of the country, which at that time was still trying to be young. The influence exerted by immigrants from Arab lands on revolutionary figures created a lot of turmoil in various regions which was then used by a group of people who had interests to replace Pancasila with Islamic law. The emergence of this group is considered the forerunner of the growing understanding of radicalism in Indonesia. After 75 years of Indonesia's independence, it seems that the development of radicalism is continuing. This is what then gave rise to a new classification relating to the period of development of radicalism in Indonesia. This period was later called the Old Radicalsm and New Radicalsm.